Performance Assessment with Data Envelopment Analysis in Public Administration in Turkey: An Example of the General Directorate of National Property Practices - İlhan Yıldırım; Harun Tanrıvermiş; Türkay Tüdeş (Istanbul Management Journal)
Accountability and performance evaluation are needed for effective and efficient use of a country’s scarce public resources. In this study, detection procedures conducted in Treasury (or State) property of the General Directorate of National Property were taken as an example of public institution activity, and its performance was evaluated with data envelopment analysis using Efficiency Measurement System program. Activities based on the management of Treasury property were analyzed using the results of the activities of national property provincial unit in the 16 central districts of Ankara province and the Treasury property data detected from 2009 to 2013. The institution has shown similar performance results in the following years, but the data after 2013 could not be accessed due to the update activities performed in the institution’s information system program. The study concluded that 2013 was the most inactive and 2010 was the most active period based on the result determined by the amount of output performance. Consequently, management policies of Treasury property should be developed to suit the needs of the economy and increase revenue realizations because the effective use of resources determines the institution’s performance by affecting the amount of output.